THE DOMESTIC TOURISM AS A DRIVER OF LOCAL ECONOMY OF BUKHARA REGION - Azimov Kh. Otabek (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation. Among the types of tourism, domestic tourism began to play a key role as the main source of financial income from tourism activities. In the regions of the Republic of Uzbekistan, domestic tourism is poorly developed, due to the imperfect infrastructure of the industry, the mismatch of prices for tourist products with their quality, and the lack of qualified personnel. Recently, the influence of external factors, such as the turbulent geopolitical situation in a number of countries, the crisis in the economy has gained particular importance for this area [1]. For the Bukhara region, domestic tourism is one of the very important areas of tourism, which needs to be developed rapidly.